Present and future of coronary risk assessment. (8th October 2021) - Prati, Francesco; Biccirè, Flavio Giuseppe; Budassi, Simone
Abstract: The search for subclinical atherosclerosis is carried out in several arterial districts using ultrasonography and computed tomography (CT). Coronary calcium assessed by computerized tomography (calcium score) is a well-validated marker of atherosclerosis and able to correlate with the extent of coronary artery disease and the risk of cardiovascular events. The evaluation of carotid atherosclerosis by ultrasonography is a technically simple and low-cost solution. However, the literature does not provide a sufficient number of evidence to clarify the clinical impact of carotid atherosclerosis and in particular the risk of developing cardiac events. According to the researchers of the Progression of Early Subclinical Atherosclerosis (PESA) study, subclinical atherosclerosis research should preferably be carried out in the femoral district, which is more easily affected by atherosclerosis. Pending the data from the PESA study, which will better clarify the role of ultrasound applied in non-coronary districts, the coronary calcifications seems to be a reasonable solution. It is possible that in the future imaging techniques (CT-PET) capable of studying the extent and functional status of coronary atherosclerosis will further improve the identification of the risk of cardiovascular events.